Induction of Staphylococcus aureus Lactose Permease in the Absence of Glycerolipid Synthesis - Mindich, Leonard (1971)
Glycerol auxotrophs of S. aureus were isolated and shown to cease phospholipid synthesis immediately when deprived of glycerol. Second-step mutants with temperature-sensitive inducibility of the lac system were also isolated. When cells were induced by temperature shift to produce the products of the lac system in the absence of glycerol, the permease activity, relative to 6-phospho-β-galactosidase activity, was between 30 and 50% that of glycerol-supplemented cultures. However, the phosphotransferase activity for β-galactosides in isolated membranes was found to be normal when compared to the level of β-galactosidase. This indicated that the permeation system was induced and integrated into the membrane, but did not function efficiently for transport. Readdition of glycerol in the presence of chloramphenicol resulted in a slow increase in efficiency of the transport activity. Glycerol deprivation after induction led to a small loss of permease efficiency.